Isolated line shape of methane with various collision partners. (December 2016) - Le, Tuong; Fissiaux, Laurent; Lepère, Muriel; Tran, Ha
Abstract: In this work, the spectral profile of an isolated transition of methane broadened by Ar, N2, O2 and He was studied using different line-shape models, from the simple Voigt to the recently recommended Hartmann–Tran profiles. For each collision-partner, absorption spectra of the ν4 2A11-3A21 line of methane were measured at room temperature and pressures ranging from 28.26 to 95.50 mbar, with a high resolution tunable diode laser spectrometer. The spectroscopic parameters of each line-shape model used were then retrieved from measured spectra using a multispectrum fitting procedure. The obtained results show that the Voigt profile leads to large deviations with respect to the measured one and that non-Voigt effects are more important for CH4 diluted in Ar, N2 and O2 than in He. We also confirm that both the confinement narrowing and the speed dependence effects must be taken into account in order to correctly reproduce the experimental spectra. In addition, the determination of the instrumental distortions of the spectrometer is also presented and discussed as a main difficulty of this analysis. Highlights: Line shape of an isolated line of CH4 broadened by Ar, N2, O2 and He was studied. High resolution absorption spectra were measured using a TDL spectrometer. Instrument line shape was taken into account. Analysis was performed using various line-shape models including the VP and the HTP. It is shown that non-Voigt effects are more important for CH4 in Ar, N2 and O2 than in He. Both speed dependences and Dicke narrowing effects affect the observed line shapes.